2004
DOI: 10.1124/dmd.104.000661
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Drug Interaction Between Valproic Acid and Carbapenem Antibiotics in Monkeys and Rats

Abstract: ABSTRACT:The Ministry of Health and Welfare, Japan banned coadministration of carbapenems, such as panipenem/betamipron (PAPM), meropenem (MEPM), and valproic acid (VPA) because clinical reports have indicated that the coadministration caused seizures in epileptic patients due to lowered plasma levels of VPA. In this study, we have clarified the mechanism of the drug-drug interaction using PAPM In vitro experiments using monkey liver slices suggested that the apparent synthetic rate of VPA glucuronide (VPA-G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 9 publications
(9 reference statements)
1
45
0
Order By: Relevance
“…These activities were inhibited by MEPM (Fig. 2, A and B) as reported previously (Nakajima et al, 2004;Nakamura et al, 2008). 4-MUG and MFA-G were used as authentic substrates to examine whether MEPM inhibits the deconjugation of other glucuronides.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…These activities were inhibited by MEPM (Fig. 2, A and B) as reported previously (Nakajima et al, 2004;Nakamura et al, 2008). 4-MUG and MFA-G were used as authentic substrates to examine whether MEPM inhibits the deconjugation of other glucuronides.…”
Section: Resultsmentioning
confidence: 98%
“…It can also be concluded that the putative enzyme is pH-sensitive but insensitive to SL. Concerning the subcellular localization of VPA-G deconjugation activity, it is reported that the activity is higher in the dmd.aspetjournals.org liver cytosol fraction than in the liver microsome fraction (Nakajima et al, 2004;Nakamura et al, 2008), where ␤-glucuronidase is enriched (Medda and Swank, 1985;Shipley et al, 1993). Considering the inhibitor sensitivity and subcellular localization of the activity, it is not likely that ␤-glucuronidase is the predominant enzyme involved in the deconjugation of VPA-G. VPAGase may be relatively selective for VPA-G, because it is not involved in the deconjugation of other glucuronide conjugates, including 4-MUG and MFA-G (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in valproic acid is a carbapenem class phenomenon thought to involve inhibiting the hydrolysis of valproic acid glucuronide to valproic acid. 130 Plasma concentrations of valproic acid are reduced by coadministration of doripenem. Reduction in serum valproic acid concentrations to below the therapeutic concentration range (50 to 100 µg/mL) was observed by 12 hours after initiation of doripenem in healthy subjects coadministered both drugs.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%